36 Volt Electric Bike Performance Analysis - Anggun Angkasa Bela Persada; Yulima Melsipa Lingga (PT FORMOSA CENDEKIA GLOBAL, 2022)
Fuel oil (BBM) is a type of non-renewable fuel so that its availability will eventually run out, to overcome this it is necessary to conduct research that can use environmentally friendly energy, one of which is electricity. In recent years, the development of electric power-based vehicles has increased rapidly, both for lighting, transportation, and so on. Electric bicycles are an example of a means of transportation that uses electricity and is environmentally friendly. This bicycle can be used by anyone and can be taken anywhere besides being relatively inexpensive, making it an effective, efficient and environmentally friendly means of transportation. The bicycle propulsion system uses a BLDC electric motor which is controlled by the ECU and throtle. Where electrical energy is stored first in a battery/battery and then flowed to the BLDC electric dynamo so that the bicycle wheels can rotate. Based on research results, electric bicycles can travel at a maximum speed of 22.22 km/hour